COMPETITIVENESS OF REGIONAL UNIVERSITIES: CONSIDERATION OF THE VIEWS OF CONSUMERS - I. V. Zakharova (Вестник университета)
It has been indicated to the differences in the meanings of the concept of “competitiveness of the University” in the context of state educational policy, macroeconomics, international and national education markets and in the context of regional consumer markets. The necessity of taking into account the consumer rating of universities in the regional market for the forecast and formation of demand for educational products of universities has been substantiated. The results of the analysis of the market of higher education in the Ulyanovsk region in the 2018-2019 academic year have been adduced. The assessment of consumer preferences of universities of the Ulyanovsk region has been made, the professional interests of school leavers have been determined. The author’s method of evaluation of competitive positions of universities, based on the coefficients of acceptance, rejection, indifference, has been explained. A discrepancy in consumer assessments of educational institutions among school leavers and their parents has been noticed, which confirms the phenomenon of inertial competitiveness of universities. The regularities of the formation of demand for educational programs of regional universities, the factors and risks of their development in the current socio-economic situation have been specified.